In praise of strangeness. : Exploring the hermeneutical potential of an unlikely source - Lategan, Bernard C (Stellenbosch Theological Journal, 2018)
In a field already investigated extensively, the article focuses on a particular aspect, namely on the nature of the interaction between the self and the other. The leading question is: What is the hermeneutical potential of the other and the stranger in relation to the self? The following dimensions are examined: the direction of flow of the interaction, the power relations involved in the process, the claim of the other on the self and the existential dimensions of strangeness. The first section examines various approaches to the other in a number of disciplines: anthropology and ethnology, art and art history, religion, philosophy, communication theory, and pedagogy. Several common traits are evident: The flow of action is pre-dominantly from the self to the other; the power relationship is unequal, skewed in favour of the self; the other is rarely perceived in his or her own right but is compared with the self who serves as norm; and strangeness is seen as inherently problematic and accompanied by negative connotations. There is consequently a constant attempt to scale down differences and to domesticate the other by various means. An alternative approach aims at reversing the normal power relationship and releasing the potential of change for the self in the encounter with the other. This requires a conscious decision to change the direction of action - from the other to the self and not vice versa. Furthermore, to break the binary hold of subject on object, the decentring of the subject is necessary. This requires the recognition of the "incompleteness" of human existence (Nyamnjoh) which opens the self for new possibilities. Acceptance of the radical openness of systems (in this case the "system" of human relationships) is the key to release the "excess"of potential available to the self in the encounter with the other and with what is strange and alien. In this context, the strategies of liberating and of enrichment through the other becomes important. Even when considering the dark side of strangeness, these strategies still apply and illustrate more clearly the existential necessity of strangeness. The potential of the other and of strangeness for liberating and enriching the self remains undervalued.